(Listeria in food industry) - Sri Esti Rahayu (Warta Industri Hasil Pertanian, 1992)
Listeria is a psychrotrop pathogenic bacteria which recently obtained much attention from food tecnologists as well as food industries due to its unique characteristic and yhe disease resulted.The following article discuss briefly about the bacteria especially its characteristics, effect,occurence,effectsof proccesing and environment, and control.